Basic Needs of Mothers with Children Undergoing Hemodialysis: A Meta-synthesis of Qualitative Studies - Tayebe Pourghaznein; Zahra Sadat Manzari; Abbas Heydari; Mojtaba Mousavi Bazaz (Mashhad University of Medical Sciences, 2019)
Background: Mothers of children undergoing hemodialysis encounter severe changes in their daily lives. It is of utmost importance to raise the awareness of treatment teams about the needs of these specific groups of mothers and different problems they may experience. The reason is that it can help health care professionals to support the mothers to fulfill their roles as the primary caregivers of such children. Aim: This study aimed to identify basic needs in mothers of children undergoing hemodialysis. Method: This meta-synthesis review of qualitative studies investigating the needs and experience of mothers whose children had kidney disease and published from January 1997 to October 2017. The articles were searched in four databases, including Web of Science, EMBASE, PubMed, and ProQuest. The search process was accomplished using the keywords "chronic kidney disease," "hemodialysis," "children," "mothers," "parents," "caregivers," "needs," "experiences," "perspectives," and "perceptions". Finally, 7 articles were chosen out of 567 papers and theses. The MAXQDA software was used to facilitate data management. Results: The systematic review of the qualitative studies revealed three main themes, including the need for child care management skills, the need to maintain family cohesion, and the need for emotional-psychological support. Implications for Practice: Mothers of children under hemodialysis should be considered as nursing clients. Accordingly, a multidisciplinary team can empower mothers to take care of the children under hemodialysis and preserve family coherence, as well as supporting them emotionally and psychologically.